Thermo-electrical and structural properties of Gd2O3 and Lu2O3 double-doped Bi2O3 - Polat, Yasin; Akalan, Hicret; Ari, Mehmet (Pergamon-Elsevier Science Ltd, 2017)
Gd2O3 and Lu2O3 double-doped Bi2O3 compounds were prepared by solid-state synthesis techniques. Eight micro crystalline samples were synthesized with compositions of (Bi2O3)(1-x-y)(Gd2O3)(x)(Lu2O3)(y), where x = 0.05, 0.1 and y = 0.05, 0.1, 0.15, 0.2. The structure of the ceramic materials was characterized by X-ray powder diffraction (XRD) and Thermo Gravimetry/Differential Thermal Analysis (TG/DTA). The morphology of the materials of the system was displayed by Scanning Electron Microscope (SEM). Also, the electrical conductivity of the samples was determined by the DC four-point probe technique (4PPT) in air at temperatures ranging from room temperature to 1100 degrees C. It was observed that two samples, (Bi2O3)(1.-x-y)(Gd2O3)(x)(Lu2O3)(y) x = 0.05-0.1, y = 0.05 have mixture phases including delta-phase before additional heat treatments, and that the phases of all of the samples changed to the stable fluorite type face centered cubic delta-Bi2O3 phase which has a high conductivity property after electrical conductivity measurements. The DTA results also showed that all samples have delta-Bi2O3 phases. The highest electrical conductivity was seen for the sample of the (Bi2O3)(0.85)(Gd2O3)(0.1)(Lu2O3)(0.05) system as 9.20 x 10(-2) (ohm.cm)(-1) at 650 degrees C. The lowest activation energy was also calculated for the sample of the (Bi2O3)(0.8)(-Gd2O3)(0.1)(Lu2O3)(0.1) system as 0.5104 eV. The results indicated that the stable delta-Bi2O3 phase samples can be used as electrolyte materials in solid oxide fuel cells. (C) 2016 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: SOFC; delta-Bi2O3; Activation energy; Ceramic electrolytes